2010
DOI: 10.1186/1471-2407-10-293
|View full text |Cite
|
Sign up to set email alerts
|

Inoculated mammary carcinoma-associated fibroblasts: contribution to hormone independent tumor growth

Abstract: Background: Increasing evidence has underscored the role of carcinoma associated fibroblasts (CAF) in tumor growth. However, there are controversial data regarding the persistence of inoculated CAF within the tumors. We have developed a model in which murine metastatic ductal mammary carcinomas expressing estrogen and progesterone receptors transit through different stages of hormone dependency. Hormone dependent (HD) tumors grow only in the presence of progestins, whereas hormone independent (HI) variants gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…We are not able at the present stage of the investigation to assess the origin of these fibroblasts. A murine origin has been described for the CAF [8,[33][34]. IBH-6 epithelial tumor cells continue to express in vivo the 2B and 2C subtypes, already described in cell culture [17].…”
Section: Discussionmentioning
confidence: 97%
“…We are not able at the present stage of the investigation to assess the origin of these fibroblasts. A murine origin has been described for the CAF [8,[33][34]. IBH-6 epithelial tumor cells continue to express in vivo the 2B and 2C subtypes, already described in cell culture [17].…”
Section: Discussionmentioning
confidence: 97%
“…FGFs have been reported to promote angiogenesis independently of VEGF [ 71 , 81 ]. Giulianelli et al demonstrated that CAFs from hormone-independent tumors express higher levels of FGF-2 than CAFs from hormone-dependent tumors in breast cancer [ 82 , 83 ]. SDF-1 secreted by CAFs also contributes to angiogenesis.…”
Section: The Role Of Cafsmentioning
confidence: 99%
“…Among the possible mechanisms behind CAF-mediated tumor growth regulation in vivo , it has been frequently observed an enhancement of angiogenesis during early phases of tumor formation via secretion of miscellaneous CAF-derived factors, including SDF-1/CXCL12 35 , CXCL14 39 , FGF-2 40 41 , PDGF 42 , IGF2 43 , TGFβ 44 45 or CTGF 46 . Alternative suggested mechanisms are increased deposition of basement membrane components in tumors 30 , expression of fibroblast activation protein (FAP-1) 47 , metalloproteinase 2 (MMP-2) 48 or cofilin-1 and IL-6 49 .…”
Section: Discussionmentioning
confidence: 99%